Desarrollo socio-afectivo y su incidencia en el comportamiento de los estudiantes del 10º año A de educación básica superior del colegio particular San Benildo La Salle en la ciudad de Guayaquil 2016 – 2017 - Martínez Amaya, Karina Yesenia (2016)
This project of investigation covers the socio-effective development, and its incidence in the behavior from the students of 10th grade parallel “A” Colegio Particular San Benildo “La Salle” in the city of Guayaquil 2016-2017, witch main problem presents in ¿How does the socio-effective development influence in the behavior of the students? Establishing the objective of analyzing the socio- effective development and its incidence in the behavior of young students. Also it pretends to bring strategies that allows them to use the socio-effective abilities in their daily life. The effective abilities reach to obtain a significate role in the life of the individual because it produces feelings and emotions in the daily life…..